Performing nature of architecture: visual and performing arts building as a tool to regenerate civic place in Alexandra - Tembo, Nyatowani L (My University, 2021)
The social culture of a place helps to define and form its character, image and identity (Landry,2010). The motive to build rich sensory experiences and environments in conjunction with the built form, offers a possible solution for the township of Alexandra to establish a space that fosters common value through cultural awareness and civic identity. Communities in South Africa are expanding and experiencing urban sprawl and population pressure. The need for coordinated growth of cultural and public spaces in townships such as Alexandra is often ignored. In such developments, residential, commercial and other types of work are placed at the forefront. Little attention is given to the cultural and public realm. The Alexandra township is still one of the most underprivileged and neglected settlements with very few public facilities, amenities and public space. The quality of its infrastructure is poorly maintained and does not meet the requirements of a society that is modernising. There are very few gathering places for the community to share their creations and display their identity. The schools in Alexandra also do not provide quality visual and performing arts education, primarily due to lack of funding. The research will investigate the role of a visual and performing arts building in Alexandra and how it can be used in urban regeneration, spatial activation, improving cultural capacity, and enhancing the civic engagement of the community. This research study has identified the Rotary square and the adjacent site across 6th Avenue within the Alexandra precinct, as a case study. This precinct is in dire need of an architectural response that can effectively contribute to the spatial character of this urban precinct and act as a catalyst for sustainable urban regeneration, and cultural and civic engagement in the community
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021